Analysis of Gas Explosion Consequence Models for the Explosion Risk Control in the New Gas Energy Filling Stations - Dan, Seungkyu; Moon, Dong Ju; Yoon, En Sup; Shin, Dongil (AMER CHEMICAL SOC, 2013)
New sorts of energy are emerging as alternative clean fuel for transportation, power generation, and household. Using the DME-LPG mixture or HCNG is being considered and investigated as an improved option for the satisfaction of regulations over current policy of using LPG or CNG. In this research, we compare the safety of mixture fuels and existing fuels in the perspective of explosion risk that would be the biggest concern in the operation of new-energy stations. The explosion risk is analyzed and compared by using three different representative models: empirical, phenomenological, and CFD-based models, ordered in increased model complexity and computational and modeling efforts. Maximum overpressures of explosion of mixture and existing fuels respectively show similar results, in all three models, and no additional risk is expected in the modified use of current refueling facilities. CFD-based explosion simulation is determined to be used in deciding the exact overpressure distribution and optimal installation of prevention equipment, and a guideline is suggested. The final results are being adopted as part of new safety regulations for existing mixture stations and will be adapted at the new facilities in Korea. As a simple way to enable legacy models to estimate the dynamic consequence by explosion, a modified code that combines a gas dynamics solver with an empirical model is also suggested.
Keywords: SIMULATION; FIRE